El pasado como capital político. Usos y disputas de la historia, grupos subalternos y conmemoraciones nacionales en Colombia (2019) y México (2021) - Sebastián Vargas Álvarez (Cahiers des Amériques Latines)
In 2019, Colombia commemorated the bicentennial of the Battle of Boyacá, a decisive event in the country's Independence .process, while in Mexico, in 2021, a triple commemoration took place: the 200th anniversary of the Consummation of Independence, the 500th anniversary of the capture of Tenochtitlán by the Spanish conquistadors, and the 700th anniversary of the founding of that city, capital of the Mexica empire. This paper describes and analyzes the main discourses and commemorative actions that the Colombian and Mexican governments deployed in the public sphere on the occasion of the aforementioned anniversaries. Specifically, the aim is to explain how (and for what purpose) groups historically invisible or marginalized from national narratives, such as indigenous and Afro-descendant communities, women and other subaltern groups, were represented in the official commemorative device, as well as the ways in which these groups and other social actors participated (or not) in the debates on the meaning of the past during the commemorations. Both cases are studied from a comparative and global perspective, which takes into account the particularities of each country, but transcends them in order to apprehend the geopolitical dimensions of the celebrations and some general trends.